Factors influencing seasonal influenza vaccination behaviour among elderly people: a systematic review. (March 2018) - Kan, T.; Zhang, J.
Abstract: Objectives: To explore the behaviour-related factors influencing influenza vaccination among elderly people using a framework derived from the Health Belief Model (HBM) and the Theory of Reasoned Action (TRA). Study design: Systematic review. Methods: Five databases were searched using predetermined strategies in March 2016, and 1927 citations were identified. Articles were selected according to inclusion and exclusion criteria. Key information was extracted from selected studies using a predesigned sheet. Both authors assessed study quality using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) or Critical Appraisal Skills Programme (CASP) checklist. Results: Thirty-six articles were selected. A new framework was proposed that contributes to shared understanding of factors influencing health behaviour. Possible determinants of influenza vaccination among elderly people were knowledge, health promotion factors, all constructs of the HBM, and some concepts of the TRA. Key factors were threat perception, behavioural beliefs, subjective norms, recommendations, past behaviour and perceived barriers. Conclusions: This is the first systematic review to analyse the factors influencing influenza vaccination behaviour of elderly people using a framework integrating the HBM and the TRA. The framework identified key factors of influenza vaccination and presented the inter-relation of behaviour-related variables. However, further well-designed studies are required to explore the inter-relationships accurately and comprehensively. Highlights: Influenza vaccination behaviour in the elderly was associated with demographic factors, health promotion factors and knowledge. All constructs of Health Belief Model and some of Theory of Reasoned Action were included in the synthesised framework. Keys were threat perception, behavioural beliefs, subjective norms, recommendation, past behaviour and perceived barrier. Effective interventions include medical staff's recommendation, peer education, express vaccination clinic, and home visit.